Facial hemiatrophy: Review of literature and a case report - Manisha S Tijare; Sandhya Srivastav; Rajat V Misurya; Archana H Lanje; Anil Ghom (Wolters Kluwer Medknow Publications, 2011)
A case report of hemifacial atrophy is presented in this paper. It is also known as Parry-Romberg syndrome, is an uncommon degenerative and poorly understood condition. It is characterized by progressive atrophy of the skin, subcutaneous tissue, muscle, cartilage or bone; the condition can leave a marked deformity on one side of the face. The incidence and the cause of this alteration is debatable. The most common complications that appear in association to this health disorder are: trigeminal neuritis, facial paresthesia, severe headache and epilepsy. Now, plastic surgery with graft of autogenous fat can be performed, after stabilization of the disease, to correct the deformity. Orthodontic treatment can help in the correction of any associated malformation. This presentation gives a review of concern literature about the etiology, physiopathology, differential diagnosis and treatment of hemifacial atrophy.